2010
DOI: 10.21273/horttech.20.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Land Application of Compost and Other Wastes (By-products) in Florida: Regulations, Characteristics, Benefits, and Concerns

Abstract: Compost is the product resulting from the controlled biological decomposition of organic material that has been sanitized through the generation of heat and processed to further reduce pathogens as defined by the U.S. Environmental Protection Agency and stabilized to the point that the compost is beneficial to plant growth. Organic materials used for composting in Florida are mainly yard wastes (trash) and food wastes. More than 5.7 million tons of composts could be produced from yard trash and food wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In a survey conducted in the midwestern United States, %85% of the high tunnel grower respondents reported the use of organic soil amendments, with commercial composts being the top choice (Knewtson et al 2010). Although studies in Florida also demonstrated the benefits of composts in improving nutrient supply and soil organic carbon content, compost application challenges have been identified, such as cost, availability, state regulations, environmental concerns, and the unpredictability of nutrients from compost sources (Li et al 2010). Physical, chemical, and biological properties of composts are largely dependent on the feedstock and composting method used (Marshall et al 2016;Rudisill et al 2015).…”
mentioning
confidence: 99%
“…In a survey conducted in the midwestern United States, %85% of the high tunnel grower respondents reported the use of organic soil amendments, with commercial composts being the top choice (Knewtson et al 2010). Although studies in Florida also demonstrated the benefits of composts in improving nutrient supply and soil organic carbon content, compost application challenges have been identified, such as cost, availability, state regulations, environmental concerns, and the unpredictability of nutrients from compost sources (Li et al 2010). Physical, chemical, and biological properties of composts are largely dependent on the feedstock and composting method used (Marshall et al 2016;Rudisill et al 2015).…”
mentioning
confidence: 99%